PROJECT BASED LEARNING BERBANTUAN STELLARIUM UNTUK MENINGKATKAN LITERASI ASTRONOMI MAHASISWA PENDIDIKAN FISIKA - Lia Afriyanti Nasution, Dara Fitra Dwi, Rofiqoh Hasan Harahap, Elia Putri (JURNAL ILMU PENDIDIKAN, 2026)
Advancements in educational technology necessitate a transformation in higher education instructional strategies, particularly for science-based courses such as Astronomy. Research from 2024 indicates that the Stellarium application significantly enhances students' conceptual understanding in Astronomy. However, the use of this technology has not yet been systematically integrated into active learning models like Project-Based Learning (PjBL). Therefore, this study aims to develop and implement a Stellarium-based PjBL model to improve the astronomy literacy and learning autonomy of Physics Education students. This research employed a quantitative method with a pre-experimental design using a one-group pretest-posttest design. The subjects of this study were 30 students. The instrument used was a learning outcome test consisting of pretest and posttest. The results showed that the average pretest score was 52.27 and increased to 81.17 in the posttest, with an improvement of 28.90 points. The hypothesis test using a paired sample t-test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. The N-Gain value of 0.61 was categorized as moderate, indicating that the learning model was sufficiently effective in improving learning outcomes. In addition, the effect size value of 1.45 was categorized as large, indicating a strong effect of the learning model. Therefore, it can be concluded that the implementation of the Project Based Learning (PjBL) model is effective in improving students' learning outcomes in astronomy material.